Amnestic mild cognitive impairment individuals with dissimilar pathologic origins show common regional vulnerability in the default mode network - Swati Rane (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2018)
Abstract Introduction Alzheimer's and Parkinson's disease (AD and PD) are distinct disorders but share similar biomarker profiles. The regions of the default mode network are implicated in these diseases and are associated with amnestic symptoms. The role of apolipoprotein‐ε4 (APOE‐ε4), which is associated with cognitive function, is unclear in PD. Methods In this work, we evaluated cortical thickness of default mode network regions that are likely affected in both early AD and PD individuals, that is, with amnestic mild cognitive impairment. We identified the prevalence of APOE‐ε4 and evaluated its association with cortical atrophy. Results We observed significant parahippocampal atrophy and hippocampal atrophy rates in amnestic mild cognitive impairment subjects, regardless of disease origins (AD or PD). Similarly, mild cognitive impairment ε4 carriers showed significant precuneal atrophy compared with noncarriers. Discussion This work supports that converging changes to default mode network regions, especially the temporal lobe and precuneus, are shared in AD and PD.